Maternal and Placental Risk Factors for Developing Necrotizing Enterocolitis in Very Preterm Infants - Ju-young Lee; Kyo-Hoon Park; Ahra Kim; Hye-Ran Yang; Eun-Young Jung; Soo-Hyun Cho (Elsevier, 2017)
Despite the clinical relevance of necrotizing enterocolitis (NEC), it remains difficult to predict which preterm infants are more likely to develop NEC. Contrary to the neonatal risk factors for the development of NEC, little information is available regarding maternal (prenatal) risk factors. We aimed to identify maternal risk factors associated with the subsequent development of NEC in very preterm infants and to determine whether the placental inflammatory lesions were related to the NEC. Methods: This retrospective cohort study examined newborns born at < 32 weeks (n=354) between July 2003 and July 2014 at a university teaching hospital. Medical records of eligible newborns and their mothers were reviewed. Maternal blood white blood cell and differential counts were measured at admission and the placentas were examined histologically after delivery. The primary outcome measure was NEC Bell Stage≥IIa. Bivariate analyses and multivariate logistic regression were used for the statistical analyses. Results: NEC was diagnosed in 26 of 354 very preterm infants (7.3%), including 19 Stage II and seven Stage III infants. Multivariate regression analysis identified maternal neutrophil-to-lymphocyte ratio [odds ratio (OR)=1.08, p=0.002], multiparity (OR=3.41, p=0.013), and birth weight (OR=0.07 per kg increase, p=0.01), but not clinical and histological chorioamnionitis and funisitis as significant predictors of NEC. Conclusion: Maternal neutrophil-to-lymphocyte ratio, parity, and birth weight can independently predict the risk of NEC in very preterm infants, whereas clinical and histological chorioamnionitis and funisitis are not predictive of NEC.